The Impact of HRM Practices on Employees Performance: The Case of Islamic University of Gaza (IUG) in Palestine - Jouda, Akram Ali; Ahmad, Ungku Norulkamar Ungku; Dahleez, Khalid Abed (International Review of Management and Marketing, 2016)
This article examines the impact of human resource management (HRM) practices on employee's performance at Islamic University of Gaza (IUG) in Palestine. In particular, the primary data has been collected via standard questionnaires from a randomly selected sample of 115 employees (faculty and non-faculty members) of Islamic University of Gaza (IUG). The multiple regression model was used to analyze the data SPSS 22. The findings of this research study have reported that HRM practices (Recruitment and selection, training and development, compensation and incentives, performance appraisal) are positively related to employee's performance. The contribution of this study is threefold. Firstly, to investigate the relationship between HRM practices and employees performance. Secondly, this research study provides meaningful insight about HRM practices and employees performance at higher education institutions in Palestine. Third, from a practical perspective, the study draws attention to the fact that there is a need to develop HRM practices that can enhance the effectiveness and sustainability of higher education institutions in Palestine.These results of this cross-sectional study can be applicable the similar higher educational institutions in Palestine. Keywords: Human resource management (HRM) practices, Employee performance, Islamic University of Gaza, Palestine JEL Classifications: M51, M52, M53